1984
DOI: 10.1182/blood.v63.1.162.bloodjournal631162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transfusion therapy on arteriographic abnormalities and on recurrence of stroke in sickle cell disease

Abstract: Stroke is a relatively frequent and severe complication of sickle cell disease. We performed cerebral arteriograms in 30 patients with sickle cell disease to evaluate the cause of acute neurologic deficits and to assess the effects of transfusion therapy given for a year or more after the acute episode. Twenty-three patients with motor and speech deficits had multiple abnormalities of major cerebral arteries. The internal carotid and anterior and middle cerebral arteries showed stenosis and/or occlusion at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(40 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…The frequency of recurrent clinical stroke was reduced by 90% in some reports (Buchanan et al, 1983). Repeat angiograms showed absence of progression of vessel disease and occasional smoothing of previously roughened endothelium in some patients, but progression of large-vessel disease in others (Russell et al, 1984). Serial MRA con®rms a similar variability in response.…”
Section: Treatmentmentioning
confidence: 84%
See 3 more Smart Citations
“…The frequency of recurrent clinical stroke was reduced by 90% in some reports (Buchanan et al, 1983). Repeat angiograms showed absence of progression of vessel disease and occasional smoothing of previously roughened endothelium in some patients, but progression of large-vessel disease in others (Russell et al, 1984). Serial MRA con®rms a similar variability in response.…”
Section: Treatmentmentioning
confidence: 84%
“…There is an unexplained association of priapism to cerebral ischaemia (Rackoff et al, 1992). An SS family member with a stroke is a strong predictor of stroke (Powars et al, 1984(Powars et al, , 1990Russell et al, 1984;Adams et al, 1994). Haplotype of the b S gene cluster (CAR) and a gene status are important correlates of severe disease expression and stroke risk, but should not be taken as the sole determinants for initiation of therapy (Powars et al, 1990;Adams et al, 1994;Figueiredo et al, 1996).…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic or environmental risk factors may influence the risk of stroke in SCD. Anecdotal reports have described the occurrence of stroke in multiple family members with SCD (Russell et al, 1984), and a recent sibling pair analysis more formally demonstrated an increased risk of stroke in siblings with SCD (Driscoll et al, 1997), supporting the presence of either genetic or environmental risk factors. Different human leucocyte antigen (HLA) genotypes have also been associated with either an increased or decreased risk of stroke in SCD (Styles et al, 2000), further suggesting the existence of genetic modifiers.…”
mentioning
confidence: 99%